ANALISIS EFEKTIVITAS PROGRAM YOUTH ENTREPRENEURSHIP AND EMPLOYMENT SUPPORT SERVICES (YESS) DALAM MENDUKUNG REGENERASI PETANI MUDA DI KABUPATEN TULUNGAGUNG (Analysis Of The Effectiveness Of The Youth Entrepreneurship And Employment Support Services (Yess) Program In Supporting The Regeneration Of Young Farmers In Tulungagung Regency) - WIDHYARIE, YUSNITA; ASNAH, ASNAH; DYANASARI, DYANASARI (Universitas Mulawarman (University of Mulawarman), 2025)
This research aims to evaluate the effectiveness and impact of the YESS Program on the regeneration of young farmers in Bandung District, Tulungagung Regency, as well as analyzing the factors that influence young farmers' interest in developing businesses in the agricultural sector. The research was conducted in December 2023 using a descriptive survey method. The research sample consisted of 81 young farmers who were members of the YESS Program in Bandung District. Data analysis was carried out descriptively by calculating the percentage influence of the variables of interest, perception and role of program assistants on the regeneration of young farmers. The research results show that the interest and perception variables each have an influence of 89%, while the role of the YESS program companion has an influence of 87% on the regeneration of young farmers. Overall, the regeneration of young farmers has an effectiveness rate of 86% in supporting the success of the YESS Program. The conclusion of this research is that the YESS Program has succeeded in encouraging the regeneration of young farmers in Tulungagung Regency with very effective results. This program contributes to increasing the younger generation's interest in agriculture, positive perceptions of this sector, and provides a significant role through mentoring.